Analisis UI/UX Dalam Perspektif Antropologi Menggunakan Metode Design Thinking Untuk Website eL TV Balai Diklat Keagamaan Palembang - Angga Madona; Tata Sutabri (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
Digitalization is the main pillar of change in various aspects of life, including education and social interaction. Balai Diklat Keagamaan Palembang has adopted digital transformation through the development of eL TV, a digital learning platform. This research aims to analyze the User Interface (UI) and User Experience (UX) on the eL TV website of the Palembang Religious Education and Training Center from an anthropological perspective using the Design Thinking method. This approach integrates aspects of culture, habits, and user behavior to create socially and contextually relevant designs. The research stages include Empathize through observations and interviews to understand user needs, Define to identify key problems, Ideate to generate creative solutions, Prototype to build an initial design that is responsive to local values, and Test to measure the effectiveness of the new design. This research concludes that an anthropological approach to UI/UX design through the Design Thinking method can increase user relevance and satisfaction with the eL TV website, while encouraging the use of technology that is more inclusive and oriented to the needs of local communities.